1969
DOI: 10.1677/joe.0.0430197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ovarian Steroids and Neurohypophysial Hormones on the Oviduct of the Viviparous Lizard, Klauberina Riversiana

Abstract: Arginine vasotocin was consistently more potent than oxytocin in its ability to elicit contractions of the oviduct of the viviparous Island Night Lizard, Klauberina riversiana, in vitro, regardless of whether the animals had previously received oestrone, progesterone or long photoperiods for 10\p=n-\20 days, sufficient to produce marked effects on body, oviduct, or fat body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1970
1970
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Several investigators have examined the effect of progesterone and the role of the corpora lutea on parturition in live-bearing snakes (Clausen, 1940;Frankel, Martins & Mello, 1940;Bragdon, 1951) and viviparous lizards (Panigel, 1956;Callard, Bayne & McConnell, 1972a) and it is generally agreed that removal of corpora lutea or ovariectomy prevents parturition, presumably due to the absence of the ovarian steroids. It is well established that oestrogen stimulates growth of the reptilian reproductive tract (see Callard & Klotz, 1973, for review), but the role of steroids in the control of oviductal contraction has only been investigated by LaPointe (1969) using the lizard, Klauberina riversiana. In this study, neither oestrone nor proges¬ terone, when injected in vivo, were shown to modify oviductal contractions in response to neurohypophysial hormones in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigators have examined the effect of progesterone and the role of the corpora lutea on parturition in live-bearing snakes (Clausen, 1940;Frankel, Martins & Mello, 1940;Bragdon, 1951) and viviparous lizards (Panigel, 1956;Callard, Bayne & McConnell, 1972a) and it is generally agreed that removal of corpora lutea or ovariectomy prevents parturition, presumably due to the absence of the ovarian steroids. It is well established that oestrogen stimulates growth of the reptilian reproductive tract (see Callard & Klotz, 1973, for review), but the role of steroids in the control of oviductal contraction has only been investigated by LaPointe (1969) using the lizard, Klauberina riversiana. In this study, neither oestrone nor proges¬ terone, when injected in vivo, were shown to modify oviductal contractions in response to neurohypophysial hormones in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It appears from studies on fish (Heller, Leathers & Lane, 1971 ;Heller, 1972) and amphi¬ bians (Heller, Ferreri & Leathers, 1970;Heller, 1972) as well as reptiles (Clausen, 1940;Panigel, 1956;Munsick, Sawyer & van Dyke, 1960;LaPointe, 1964LaPointe, , 1969) that neuro¬ hypophysial hormones are involved in the control of the expulsion of eggs and young from the reproductive tract of lower vertebrates. To our knowledge, a direct involvement of the ovarian steroids in the control of oviduct contractility in lower vertebrates has not hitherto been demonstrated and the present data suggest actions of oestradiol and progesterone on the turtle oviduct which are similar to the actions of these hormones on the mammalian uterus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore predicted that genetic variation will be more common in protein and large polypeptide hormones than in the neurohypophysial octapeptides. However, because of their relative simplicity the neurohypophysial hormones still offer the best prospects of understanding the evolution of hormonal function in relation to hormonal structure (LaPointe, 1969). For example, the evolution of the hormonal system as a whole can be discussed in terms of the affinities of target organs for hormonal variants which do differ significantly in their biological proper¬ ties.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is only scanty evidence that-by analogy with the mammals-they might also be involved in reproductive processes in lower vertebrates. The hormone content of the posterior lobe of birds changes during the egg-laying cycle (Legait, 1959;Tanaka & Nakajo, 1962) and the oviduct of birds (McKenney, Essex & Mann, 1932;Munsick, Sawyer & van Dyke, 1960;Munsick, 1965;Rzasa, & Ewy, 1968) and reptiles (Clausen, 1940;Panigel, 1956;Munsick et al 1960;LaPointe, 1964LaPointe, , 1969 responds to neurohypophysial hormones in vivo and in vitro. The aim of the present study was to investigate the effect of neurohypo¬ physial hormones on amphibian oviducts.…”
Section: Introductionmentioning
confidence: 99%